Thomas Mann’s "The Magic Mountain" (1924): A questioning of health, rationality, and the romantic tradition - Kosecki, Krzysztof (Categories and Units in Language and Linguistics, 2020)
Thomas Mann’s (1875–1955) epic novel The Magic Mountain (1924/1996) turns upside down the conventional axiology of the experiential categories of health and rationality, as well as of the romantic idea of a Bildungsreise or educational journey. The complex narrative describes a profound personal change of the main hero Hans Castorp, which takes place in opposition to the values of the conventional bourgeois society and against the background of the social and political condition of Europe on the verge of World War I.